If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -6c = n Solving 5a + -6c = n Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6c' to each side of the equation. 5a + -6c + 6c = 6c + n Combine like terms: -6c + 6c = 0 5a + 0 = 6c + n 5a = 6c + n Divide each side by '5'. a = 1.2c + 0.2n Simplifying a = 1.2c + 0.2n
| 10x+5=2x-9 | | 82=(5x-40) | | -15c+4a=m | | 0=8x^2-14x | | 2g+12=3G-1 | | 5+-3a=n | | 61=(94x-20) | | 15x-120=6x-90 | | 2y-8x=-18 | | -.30(x-9)=-.50 | | 7x-(2x+7)=8x-46 | | 8+8=a | | (3x+18)(3x+18)=36 | | 4-2a=m | | 3x^2-12x+2x-8= | | 8x-(4x+6)=10 | | (3n+2)=0 | | 2(7x-1)=29 | | x^2+14=9x | | -3x+5=-3 | | -75y+.25=.50 | | 4x+2=21 | | (2a-4)=m | | -q+5=10 | | p+.30p=666666667 | | K-3k+3=11 | | 9y^2-y= | | -y-3=8 | | 7d-13=17+3d | | 3(x+1)-7=20 | | 4x^2+7x=0 | | -x+100=100 |